The Use of Digital Evidence in Human Trafficking Investigations - Chen, Isabella; Tortosa, Celeste (Anti-Trafficking Review, 2020)
This short article two NGO workers’ experience providing legal and social support to twenty Venezuelan women who were trafficked through the use of social media and chat apps. It shows how the digital evidence from online interactions between the women and their traffickers was used in the investigation and successful prosecution of the case. The article concludes, however, that this does not apply to all women that the NGO supports, and thus digital evidence, and technology, have only limited application in anti-trafficking efforts.